Method of accelerated modular exponentiation based on dynamic pre-calculation tables - Rusanova, O.V.; Markovskyi, O.P.; Haidukevych, O. (Problems of Informatization and Management, 2025)
A method for accelerated calculation of the modular exponent has been theoretically substantiated, developed and investigated, the difference of which is that in each iteration, recalculations are performed, which allow performing modular operations of multiplication and squaring with group processing of bits in both phases: multiplication itself and Montgomery reduction, due to which the time for implementing exponentiation is reduced. Acceleration is achieved by forming recalculation tables at each iteration of the expo-nentiation algorithm. The paper theoretically substantiates this possibility by using the built-in RAM of the terminal device, provides a detailed description of the method, the operation of which is illustrated by a numerical example, and presents a detailed assessment of its effectiveness. It is theoretically and experimentally shown that the proposed method allows for 5 times faster modular exponentiation compared to known methods for its implementation on terminal devices in IoT technologies.